Implementation of Kosa Rupa Book: Drawing and Coloring of Elementary School Teachers in Pegayaman Village, Bali - Alhail, Hadi; Rubijanto, Vincensius Jovan; Musthafa, Akram; Purnama, Della; Utama, I Gusti Agung Gede Aditya (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Difficulty in teaching learning related to drawing from teachers to students is a problem experienced by elementary school teachers in Pegayaman Village, previous research provides information that there is one media to help teachers improve their drawing and coloring competencies, namely